AN ANALYSIS RATE OF RETURN TO EDUCATION INVESTMENT IN GRADUATES OF ENGLISH EDUCATION DEPARTMENT (STUDY OF HIGHER EDUCATION AT WEST JAVA AND BANTEN PROVINCE) - Devika Putri Kistiani; Johar Permana; Taufani Chusnul Kurniatun (Jurnal Administrasi Pendidikan, 2020)
The purpose of this research is to find out how the level of return on education investment and the results of human resource analysis using the Payback Period, Net Benefit or Cost Ratio, and Net Present Value methods for graduates in the English Education Department of Higher Education at West Java and Banten Province. The method used in this research is descriptive quantitative method. Samples taken in this study were 60 graduates in the English Education Department of Higher Education at West Java and Banten Province. Based on the results of the research, obtained 3 domiciles from all respondents, namely Banten, DKI Jakarta, and West Java provinces. The results showed that there was a high income gap be- tween graduates in each domicile. Using the Payback Period method, for graduates who are domiciled in Banten and West Java province, showed that investment is feasible but for graduates who are domiciled in the DKI Jakarta province, showed that unfeasible. Using the Net Benefit or Cost Ratio (BCR) method, for graduates domiciled in Banten and West Java province indicate that the investment is feasible, that the BCR value is more than 1. However, for graduates who are domiciled at the DKI Jakarta province, that the investment is unfeasible, that the BCR value is less than 1, that is 0.30. Using the Net Present Value (NPV) method, for graduates who are domiciled at Banten and West Java province showed that the in- vestment is feasible, that a positive NPV value. However, for graduates who are domiciled in DKI Jakarta province, showed that the investment is unfeasible, that the NPV value is negative.